Adsorption capacity of oxidized nitrogen-doped bamboo-like carbon nanotubes. Issue 12 (1st October 2020) - Vanyorek, László; Muránszky, Gábor; Fiser, Béla; Sikora, Emőke; Hutkai, Zsuzsanna G.; Viskolcz, Béla
Abstract: Nitrogen-doped bamboo-like carbon nanotubes (N-BCNTs) were synthetized by catalytic chemical vapor deposition (CCVD) and characterized by electron microscopy. The produced nanotubes were oxidized in different degree by using of various oxidizing agents (H2 O2, HClO4 and HNO3 ) in order to change their adsorption potential by creating dissociable functional groups ( e.g. -OH) on their surface. The appearance of oxygen containing groups was confirmed by spectroscopic analysis and the zeta potential (ζ of the samples was measured. The HNO3 treatment has led to the emergence of the most polar groups on the nanotube surface (ζ = −27.1 mV), while the other two oxidizing agents were less effective (H2 O2 and HClO4, ζ = −18.3 and −19.8 mV, respectively). The adsorption potential of the oxidized N-BCNT samples were tested with copper(II)-ion. Despite the difference in their surface properties, the oxidized nanotubes adsorbed copper to the same extent. The contribution of the oxidized surface for the adsorption capacity is smaller than the effects of nitrogen doping. Thus, more things involved in the adsorption mechanism not only electrostatic attraction, but sorption-precipitation, and complex formation between copper and heteroatoms of the nanotubes. Thus, it is not enough to discuss the effect of dissociable functional groups, but the contribution of e.g. heteroatoms must also be taken into account to fully understand metal ion adsorption on oxidized carbon materials. Graphical Abstract: